A novel series of putative Brugia malayi histone demethylase inhibitors as potential anti-filarial drugs - Tamara Kreiss; Tyler Eck; Brittany Hart; Sreedhar Tummalapalli; David Rotella; John Siekierka (Public Library of Science (PLoS), 2022)
Filariasis, caused by a family of parasitic nematodes, affects millions of individuals throughout the tropics and is a major cause of acute and chronic morbidity. Current drugs are largely used in mass drug administration programs aimed at controlling the spread of disease by killing microfilariae, larval forms of the parasite responsible for transmission from humans to humans through insect vectors with limited efficacy against adult parasites. Although these drugs are effective, in some cases there are toxic liabilities. In case of loiasis which is caused by the parasitic eyeworm Loa loa, mass drug administration is contraindicative due to severe side effects of microfilariae killing, which can be life threatening. Our screening program and medicinal chemistry efforts have led to the identification of a novel series of compounds with potent killing activity against adult filarial parasites and minimal activity against microfilariae. A structural comparison search of our compounds demonstrated a close structural similarity to a recently described histone demethylase inhibitor, GSKJ1/4 which also exhibits selective adult parasite killing. We demonstrated a modification of histone methylation in Brugia malayi parasites treated with our compounds which might indicate that the mode of drug action is at the level of histone methylation. Our results indicate that targeting B. malayi and other filarial parasite demethylases may offer a novel approach for the development of a new class of macrofilaricidal therapeutics. Author summary Parasitic diseases are responsible for tremendous suffering and morbidly throughout the world. There is a need for new drugs to treat parasitic disease. New approaches aimed at treating parasitic diseases depend upon an understanding of the critical functions required for parasite survival. One such disease is lymphatic filariasis (elephantiasis), a devastating parasitic disease initiated by the bite of a mosquito carrying infectious larvae. The larvae develop into adult parasites which sequester themselves in host lymphatics where they survive for several years. We have identified a novel series of compounds which appears to affect filarial parasite epigenetic regulatory mechanisms compromising parasite survival. These compounds provide both a pharmacological probe for the study of filarial parasite epigenetic mechanisms important for survival as well as providing a potential opportunity for anti-filarial drug development. In addition, these mechanisms are present in a variety of parasitic nematodes offering the opportunity for development of treatments for a wide variety of parasitic nematodes.